Remote sensing and landscape metrics to identify and to assess site-specific damage in cultivation systems of Central Europe - Voß, Kerstin (ERDKUNDE, 2004)
For the implementation of a site-specific management an exact knowledge of the heterogeneity within the fields is necessary. Remote sensing data offers the possibility to identify the heterogeneity within fields with comparatively small expenditure. However, the question arises which influence scaling has on the recognition of site-specific plant damage and which spatial resolution is necessary for the identification of site-specific damage? The study introduced a methodology using landscape metrics to estimate the influence of spatial scale on the structure and identification of pathogen infestations and nitrogen stress in crops. The results indicate a useful description of the influence of scale on the identification of stress factors in winter wheat. Also it is possible to denominate a threshold value of the spatial resolution, from which site-specific plant damage cannot any longer correctly be apprehend.